LIFE AND PROFESSIONAL SELF-DETERMINATION IN THE FORMATION OF READINESS FOR FUTURE PROFESSIONAL ACTIVITY - Panchuk , Panchuk (PSYCHOLOGICAL JOURNAL, 2025)
In psychological readiness for self-determination, self-awareness plays a leading role - awareness of one's qualities and their evaluation, an idea of one's real and desired self, the level of claims, evaluation of oneself and others, introspection and personal reflection. The meaningful life activity of a higher education student reflects the process of forming values and value orientations as a stable element of life perspective. Choosing a profession is not just a choice of a field of activity, it is a determination of the path of development of one's personality, realization of one's knowledge, skills and abilities. The problems of professional self-determination come to the fore in adolescence. The most important characteristic of early adolescence is a focus on the future, which creates a positive emotional background for the individual's attitude towards himself/herself, stimulates his/her activity and is the basis for his/her development. Adolescence coincides with university studies. It is during the first year of study that a young person's attitude to learning and future professional activity is formed, an active “search for oneself” continues, and the qualities of a professionally competent modern specialist are formed. A characteristic feature of early adolescence is the formation of life goals and plans. Life plans depend on the tasks that are determined by the objective conditions of life and value orientations of a young person and are conditionally divided into: professional and educational (to get an interesting job you like, to improve your skills, to get a higher education); socio-political (to broaden your political outlook, to participate in public life); romantic and cognitive (to visit other cities and countries, to gain new impressions); personal and family (to find true friends, to start a family, to raise children as real people); material and domestic (to achieve a good financial situation, to create comfortable living conditions). The formation of successful professional self-determination of a young person requires certain mental, psychological and physical properties that meet the requirements of the chosen profession and contribute to the successful mastery of it. A young person is required to acquire such psychological qualities as the development of natural abilities, expansion and deepening of professional interests, values, moral orientations and ideals, career aspirations, professional plans, and socio-political beliefs. Developing the internal position of a future specialist, giving a professional orientation to the life aspirations and motives of a higher education student's behavior is an important point in the formation of the personality of a future specialist-philologist, the formation of stable life views and professional beliefs.